Study on natural antioxidants: sources, mechanisms of action and health benefits - Daniela Cîrțînă; Roxana-Gabriela Popa (Journal of Research and Innovation for Sustainable Society)
The role of natural antioxidants in protecting the body from free radicals is well known, and the importance of these compounds in maintaining health and preventing disease is essential. The health benefits of these compounds are numerous, the most important of which are protecting cells by neutralizing free radicals and decreasing oxidative stress at the cellular level, improving the immune system, preventing chronic diseases and slowing down the ageing process. The paper presents aspects related to the mechanism of action of natural antioxidants, their sources, antioxidant capacity and the role of natural antioxidants in the prevention of certain diseases.